Searching for perceptual similarity within, and between, the (chemical) senses. (September 2022) - Spence, Charles
In this narrative historical review, I want to take a closer look at the concept of perceptual similarity both as it applies within, and between, the chemical senses (specifically taste and smell). The discussion is linked to issues of affective similarity and connotative meaning. The relation between intramodal and crossmodal judgments of perceptual similarity, and the putatively special status of those odorants that happen to take on taste qualities will also be discussed. An important distinction is drawn between the interrelated, though sometimes distinct, notions of perceptual similarity and crossmodal congruency, specifically as they relate to the comparison of chemosensory stimuli. Such phenomena are often referred to as crossmodal correspondences, or by others (incorrectly in my view), as a kind of ubiquitous synesthesia.